2017
DOI: 10.1093/hmg/ddx063
|View full text |Cite
|
Sign up to set email alerts
|

DAPL1, a susceptibility locus for age-related macular degeneration, acts as a novel suppressor of cell proliferation in the retinal pigment epithelium

Abstract: The retinal pigment epithelium (RPE) forms a monolayer at the back of the vertebrate eye and is fundamental to retinal function and homoeostasis. During early development, RPE cells undergo rapid proliferation, but in the adult, they remain normally nonproliferative throughout life. Nevertheless, under pathological conditions such as in proliferative vitreoretinopathy or after retinal ablation, mature RPE cells can re-enter the cell cycle and form nodules or multiple cell layers. Here we show that Dapl1, whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…Our previous work has demonstrated that DAPL1 plays a critical role in inhibiting RPE cell proliferation both in vitro and in vivo (Ma et al., ). Confirming these results, the presence of Ki67‐positive cells was dramatically decreased in DAPL1 overexpressing ARPE‐19 cells (ARPE19 + DAPL1) compared with EGFP‐overexpressing control cells (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous work has demonstrated that DAPL1 plays a critical role in inhibiting RPE cell proliferation both in vitro and in vivo (Ma et al., ). Confirming these results, the presence of Ki67‐positive cells was dramatically decreased in DAPL1 overexpressing ARPE‐19 cells (ARPE19 + DAPL1) compared with EGFP‐overexpressing control cells (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Transfection with either si‐RNAs led to a partial rescue of cell proliferation (Figure c–e). Our previous work has demonstrated that DAPL1 inhibits RPE cell proliferation in part by increasing the protein levels of P21, which can downregulate the levels of p‐RB, P107, and E2F1 (Ma et al., ). To investigate whether DAPL1 mediates (−) MITF‐induced ARPE‐19 cell proliferation inhibition through the P21‐p‐RB, P107, and E2F1 axis, we analyzed the levels of these proteins in (−) MITF‐infected cells with or without knockdown of DAPL1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The death-associated protein-like 1 (DAPL1) protein, encoded by DAPL1 gene, was reported to be associated with the pathogenesis of age-related macular degeneration (AMD) [2] and the regulation of cell proliferation in the retinal pigment epithelium (RPE) [3,4]. A whole genome expression profiling data suggested that DAPL1 gene may be linked to the chewing-tobacco-associated oral cancer [5].…”
mentioning
confidence: 99%
“…This is consistent with the inability of the RPE to renew itself, once differentiation and further maturation commences (112). Few factors have been identified that can promote proliferation and expansion of RPE; these include transgenic hyperactivation of Notch signaling, resulting in microphthalmia and coloboma (29,113), or loss of factors that normally limit proliferation in the developing RPE, such as the cyclin-dependent kinase inhibitor p27Kip1 or DAPL1 (114)(115)(116). Collectively, our analysis reveals a unique role for Nf2 in regulating closure of the optic fissure by restricting RPE proliferation in the optic cup.…”
Section: Nf2 Is Required For Balancing Rpe Cell Number During Of Closurementioning
confidence: 71%